Analysis Of Benefit Level Among Employees Receiving Institution Of Social Security Employment At Hoffment Cleanindo Persero Surabaya - Priyatna, Salsabila Balqis; Mustofa, Amirul (Socious Journal, 2024)
This research aims to determine the extent to which social protection benefits contribute to maintaining the welfare of employees at Hoffment Cleanindo Persero Surabaya as users of the Institution of Social Security Employment (ISSE). The objective of this research indicates that increasing awareness and benefits are crucial to helping employees feel better and assisting the company in maintaining stability. The author employed a descriptive data analysis model supplemented by on-site observations. Interviews with employees and company executives were conducted, and direct observations were made. The collected data will be presented in graphical form with systematically structured explanations. The discussion findings reveal disparities and differences in perception between employers and workers. This research aids in identifying necessary improvements or changes to meet the needs and expectations of employees. The findings will provide better insights into how employees perceive, experience, and expect benefits from the ISSE program, thereby ensuring their welfare. The author recommends that with the ISSE program, employees can increase their awareness, and companies can pay more attention to the ISSE program to achieve the desired welfare for both employees and the company.